2019
DOI: 10.1177/1350650119868910
|View full text |Cite
|
Sign up to set email alerts
|

Influences of operation parameters on noise of journal bearing with compound texture considering lubricant thermal effect

Abstract: Effects of operation parameters on the noise of the compound textured journal bearing are analyzed using computation fluid dynamic method and broadband noise source theory. After a three-dimensional model of the compound textured bearing is established, the lubrication performances of the bearing are compared under the isothermal and thermal situations. Further, the noise performances of the textured and smooth bearings are studied at the varied operation parameter. Numerical results show that appropriately de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…[19][20][21] However, the compound texture effect on the dynamic characteristic of the journal bearing has not been studied to date. Since the compound texture shows positive effects on static performances of the journal bearing, [16][17][18][19][20][21] it is essential to explore its effect on the dynamic characteristic of the journal bearing. In the present work, the investigation of the compound texture effect on the dynamic characteristics of the journal bearing was conducted under the consideration of the elastic deformation and cavitation effects.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] However, the compound texture effect on the dynamic characteristic of the journal bearing has not been studied to date. Since the compound texture shows positive effects on static performances of the journal bearing, [16][17][18][19][20][21] it is essential to explore its effect on the dynamic characteristic of the journal bearing. In the present work, the investigation of the compound texture effect on the dynamic characteristics of the journal bearing was conducted under the consideration of the elastic deformation and cavitation effects.…”
Section: Introductionmentioning
confidence: 99%
“…In a combination of higher load and rolling speed, the surface textured contacts yielded significant reduction in rolling friction and vibration amplitude at resonant frequencies in comparison with the smooth contacts. The study of Meng et al [31] showed that appropriately decreasing the eccentricity ratio or rotational speed can reduce the noise of the compound textured bearing. In addition, there is a critical length/diameter ratio of the bearing for suppressing the noise of the compound textured bearing.…”
Section: Introductionmentioning
confidence: 99%